Bounds for Fourier-Jacobi coefficients of Siegel cusp forms of degree two - Kohnen, Winfried; Sengupta, Jyoti (L-functions and Automorphic Forms, 2017)
We discuss and prove several estimates involving Petersson norms of Fourier-Jacobi coefficients of Siegel cusp forms of degree two.